Pengaruh Komunikasi Organisasi, Karakteristik Individu, Kemampuan Kerja dan Etika Kerja Terhadap Prestasi Kerja Karyawan - Fachira, Haya; Ezzah Nahrisah; Arasy Ayu Setiamy (Forum Kerjasama Pendidikan Tinggi, 2026)
The purpose of this study was to determine the effect of organizational communication, individual characteristics, work ability and work ethic on employee performance at PT. Nusantara Plantation IV. The type of research used in this study is an associative type. The sample used is the employees of PT. Perkebunan Nusantara IV Medan with a total of 175 respondents. In this study researchers used primary data sources. The data collection technique in this study was a questionnaire. The data analysis technique used in this research is multiple linear regression test. Based on the results of the study it was found that organizational communication significantly influences employee performance, individual characteristics variables significantly influence employee performance, work ability variables significantly affect employee performance, and work ethic variables significantly influence employee performance as well as organizational communication variables. Individual characteristics, work abilities and work ethics of employees at PT. Perkebunan Nusantara IV jointly has a positive and significant effect on the performance of employees of PT. Perkebunan Nusantara IV Medan, thus the proposed hypothesis is proven.